Reposicionamento de fármacos para o tratamento da tuberculose : avaliação da atividade antimicobacteriana de compostos antimaláricos - Sidrônio, Maria Gabriella Silva (2020)
Mycobacterium tuberculosis is the pathogen that causes tuberculosis, a contagious infectious disease that spreads through the airways of infected individuals. Tuberculosis is a leading cause of death worldwide and one of the factors that contribute to this condition is the emergence of strains resistant to the recommended therapy to treat this disease. In order to reduce the high incidence rates of tuberculosis, researchers are looking for new alternatives for the treatment of tuberculose. In this sense, some studies indicate that antimalarials such as chloroquine, mefloquine and primaquine have antimicrobial activity against strains of M. tuberculosis. This study aimed to evaluate the antimycobacterial activities of primaquine, chloroquine, mefloquine and tafenoquine, in strains of M. tuberculosis and M. smegmatis mc2155. Initially, antimalarials were incubated with M. tuberculosis H37Ra and M. smegmatis, in order to determine their minimum inhibitory concentrations. The activities of the test molecules were compared with each other and with drugs used in the treatment of tuberculosis. Additionally, combinatorial tests were carried out involving the antimalarial molecule with the greatest potential, tafenoquine, and drugs used in the treatment of tuberculosis. After determining the antimalarial molecules with the greatest potential, suspensions of M. tuberculosis H37Ra were subjected to models of stress and starvation. Experiments were also carried out in order to determine a death curve for the most potential antimalarial in M. tuberculosis H37Ra. Tests were also carried out in order to determine the minimum inhibitory concentration in resistant and virulent strains of M. tuberculosis, as well as tests to determine the molecular target of the most potential antimalarial in these microorganisms. After these tests, it was possible to conclude that all drugs of primaquine, chloroquine, mefloquine and tafenoquine showed antimicrobial activity against strains of M. tuberculosis, as well as M. smegmatis, however the drugs of mefloquine and tafenoquine were considered to be greatest potential. Regarding combinatorial tests, it was possible to observe that mefloquine, when combined with tafenoquine, has a synergistic effect in M. tuberculosis. After carrying out experiments on bacteria submitted to stress and dormancy models, it was possible to observe that the drugs tafenoquine and mefloquine have antimicrobial activity in suspensions of M. tuberculosis subjected to nitrous stress and nutrient depletion. Additionally, it was possible to observe that tafenoquine, as well as mefloquine, present activity in resistant and virulent strains of M. tuberculosis. The satisfactory activity of antimalarials in strains of Mycobacterium spp. suggests that these drugs may be considered promising candidates for the treatment of tuberculosis.